Implementasi Metode Case Base Reasioning dan SUPR-Q Untuk Sistem Diagnosis Kerusakan Lokomotif CC 201 - MZ, Yumarlin; Rahayu, Sri; B, Jemmy Edwin (Jurnal Pseudocode, 2024)
The railway locomotive has undergone significant progress by transitioning from conventional systems to the use of microcontroller-based sensors. However, to expedite repairs, error identification requires continuous improvement in human resource quality and the development of application systems to assist technicians in identifying issues with the CC 201 locomotive. The system development methodology in this research adopts the waterfall approach, encompassing requirements analysis, system design, implementation, and subsequent system testing. The research aims to construct a system capable of identifying faults and aiding technicians in diagnosing and providing repair solutions for the CC 201 locomotive, utilizing the Case-Based Reasoning method. Research results indicate the system's effectiveness in diagnosing CC 201 locomotive issues based on observed symptoms. Usability testing with 20 respondents using the SUPR-Q method demonstrates excellent ease of use and system satisfaction, achieving a score of 90.86%.